FT-IR SPECTROSCOPY FOR IDENTIFICATION OF POLYSACCHARIDES ISOLATED FROM “NÍSPERO DE LA SIERRA” AND “GRANADILLA” FRUITS - Chasquibol S., N. (2010)
Fourier transform-infrared (FT-IR) spectroscopy for determination of methyl esterification degree (MED) of pectins is described. The method was used to cualitative determination of methylation level of pectins isolated from níspero de la sierra (Nespilus germánica) and granadilla (Pasiflora ligularis) fruits. All the samples used were in solid state. Qualitative determination of MED of the samples were confirmed from FT-IR and their spectra were compared against two commercial pectin standards, using two characteristic bands of strong absorbance observed at 1630 and 1745 cm-1. Under present experimental conditions these bands could be assigned to the stretching frecuencies for the carbonyl groups of galaturonic acid and its methyl ester, respectively.